CDR 2020
DOI: 10.20517/cdr.2020.61
|View full text |Cite
|
Sign up to set email alerts
|

The role of extracellular vesicles in acquisition of resistance to therapy in glioblastomas

Abstract: Glioblastoma (GBM) is the most aggressive primary brain tumor with a median survival of 15 months despite standard care therapy consisting of maximal surgical debulking, followed by radiation therapy with concurrent and adjuvant temozolomide treatment. The natural history of GBM is characterized by inevitable recurrence with patients dying from increasingly resistant tumor regrowth after therapy. Several mechanisms including inter- and intratumoral heterogeneity, the evolution of therapy-resistant clonal subpo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 156 publications
(208 reference statements)
0
22
0
Order By: Relevance
“…Exosome samples taken from blood were able to show fluctuations in MGMT and APNG levels throughout treatment that may be suggestive of resistance development [ 246 ] . This increased understanding and utilization of EVs in diagnosis is representative of the many advancements in the field of TMZ resistance and a movement towards more novel and creative solutions to glioblastoma treatment [ 247 ] .…”
Section: Alternative Mechanisms In Temozolomide Resistancementioning
confidence: 99%
“…Exosome samples taken from blood were able to show fluctuations in MGMT and APNG levels throughout treatment that may be suggestive of resistance development [ 246 ] . This increased understanding and utilization of EVs in diagnosis is representative of the many advancements in the field of TMZ resistance and a movement towards more novel and creative solutions to glioblastoma treatment [ 247 ] .…”
Section: Alternative Mechanisms In Temozolomide Resistancementioning
confidence: 99%
“…Thus, EVs originating from MES drive PN glioblastoma progression and, ultimately, drug resistance through an NF-κB signal transducer and STAT3 signaling [ 20 ]. EVs have also been found to be major players of drug resistance in glioblastomas by transporting anti-cancer agents out of the tumor microenvironment [ 21 ], highlighting the importance of targeting EVs in the endeavor of developing novel therapeutic strategies for this disease. miRNAs using EVs as their nano-vehicles in glioblastomas have been thoroughly reviewed elsewhere [ 22 ].…”
Section: Drivers Of Emt In Glioblastomamentioning
confidence: 99%
“…Glioblastoma (GBM) based radiation therapy has been shown to possess limited efficacy due to the enrichment of cancer stem cells (CSCs). CSCs have the capacity to cause recurrent rumors and are resistant to therapies usually used against GBMs (Yekula et al, 2020a). In this regard, a study by Ramakrishna et al, showed that mass exporting of miR-603 in MVs led to the treatment resistant phenotype.…”
Section: How Do Mvs Contribute Toward the Development Of Chemo And Radioresistance?mentioning
confidence: 99%